2014
DOI: 10.1111/jcpe.12264
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular reconstruction using a calcium phosphate/polyethylene glycol hydrogel carrier with BMP‐2

Abstract: Polyethylene glycol compromises the osteogenic effect of BMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…The advantage of this approach being closer to both human bone biology and a clinical scenario is counteracted by the disadvantage that intra-oral wounds may be exposed to uncontrolled chewing activity and mechanical manipulation by the animals. The increased likelihood of dehiscences in intra-oral augmentation models in minipigs has been shown previously (Gruber et al, 2014). In this study, six out of 34 sites have shown dehiscences in the augmented areas that had resulted in inferior regeneration.…”
Section: Discussionsupporting
confidence: 72%
“…The advantage of this approach being closer to both human bone biology and a clinical scenario is counteracted by the disadvantage that intra-oral wounds may be exposed to uncontrolled chewing activity and mechanical manipulation by the animals. The increased likelihood of dehiscences in intra-oral augmentation models in minipigs has been shown previously (Gruber et al, 2014). In this study, six out of 34 sites have shown dehiscences in the augmented areas that had resulted in inferior regeneration.…”
Section: Discussionsupporting
confidence: 72%
“…Although many studies indicate that PEG hydrogels lead to reduced cell adhesion [20], and may therefore affect new bone formation [19,22,36], the PEG hydrogel blocks, used in the present investigation, did not influence the distribution or enhancement of NBF after both time points. The present results indicate that unloaded PEG hydrogels themselves have no positive or negative effect on new bone formation.…”
Section: Discussioncontrasting
confidence: 58%
“…That clinical study demonstrated more favourable results when rhBMP‐2 was added to xenogeneic granules compared to a control group without the growth factor (Jung et al., ). These data were later supported by a series of pre‐clinical studies, all demonstrating the high potential of this combination for localized bone regeneration (Gruber et al., ; Schwarz et al., ; Thoma, Kruse, Ghayor, Jung, & Weber, ; Yon et al., ). Due to the size of the defect and thereby a further need of stability of the augmentation in the present study, the DBBM block was used.…”
Section: Discussionmentioning
confidence: 80%